Development and evaluation of a Wikipedia based group assessment to enhance science communication - Mroczek, Katelyn; Mitchell, Pru; McSharry, Brian Patrick; Woods, Alice; Spry, Belinda; Paustian, Timothy; Vanniasinkam, Thiru (Frontiers in Education, 2025)
This project, conducted in collaboration with Wikimedia Australia, introduced an assessment that aimed to enhance science communication skills among third-year microbiology students. With assistance from Wikimedia Australia, suitable Wikipedia articles on immunology topics were selected. All concepts had been covered in course content. Students worked in groups to evaluate these Wikipedia articles, assessing their accuracy, organization, verifiability, depth, and suitability for a general audience. Each group also generated an AI-created article on the same topic and evaluated it using the same criteria. The final report compared the AI-generated content with the Wikipedia article, focusing on key measures of science communication: accuracy, clarity, relevance, and reliability. The evaluation highlighted strengths and areas for improvement in both types of content, providing recommendations for enhancing Wikipedia articles. Students also submitted a reflection on the importance of information literacy and science communication in the digital age. After submission, a survey on students’ perspectives of the assignment was completed by 64% of the class (N = 42). Most students found the assignment to be a novel experience compared to previous tasks. Notably, 60% found it useful, and half indicated that they learned from their peers through the collaborative process. Students rated the readability of both Wikipedia and AI articles and assessed the accuracy and their suitability for a general audience. Additionally, students noted differences in output when generating AI articles, developing their AI literacy skills. The readability of Wikipedia articles compared to other scientific literature (textbooks and journal articles) was also rated, with 45% of students assessing these Wikipedia articles on immunology topics as not pitched for a general audience. By completing this assignment students reported gaining essential graduate competencies such as critical thinking, analysis, communication, and teamwork, as well as a better understanding of Wikipedia and AI. Students also shared their perspectives on whether they would consider using Wikipedia and AI for future assignments.